Case-control Study: The Effect of Exposure to Cigarette Advertisements on Smoking Behavior in School-Age Children in Batu - Hutomo, Rizky Aditya; Martini, Santi; Widati, Sri (Universitas Airlangga, 2024)
Background: Cigarette smoking is a danger that threatens the world community. Cigarette advertising content that is often aired on electronic media can provide opinions and shape the perceptions and actions of someone who sees it. Objective: This study aims to analyze the effect of exposure to cigarette advertising on smoking behavior in school-age children. Methods: This study used a case-control design. The case sample is a portion of school children aged 10-14 years who smoke in the Batu Health Office work area recorded in school-age smoking screening data as many as 81 samples. The control sample is a portion of school children aged 10-14 years who do not smoke in the Batu Health Office work area and who are schoolmates of the 81 case samples. The sampling technique was carried out by simple random sampling. Results: There is an effect of exposure to online cigarette advertisements on smoking behavior in school-age children (pvalue:0.016; OR:2.718;95%CI 1.258-5.872). Exposure to cigarette advertisements through offline media and idol figures did not show a statistically significant effect, however, based on the results of the study, showed that students who have been exposed to cigarette advertisements tend to smoke. Conclusion: Students who are exposed to cigarette advertisements through online media have a risk of becoming smokers.